Pendayagunaan Dana Zakat, Infaq, dan Shodaqoh Melalui Pemberdayaan Program Layanan Kesehatan: Studi Kasus Padalembaga Kesehatan Madani Rumah Sehat Madani Yayasan Dompet Sosial Madani Provinsi Bali - Mashuri, Eko; Wiyono, Agung; Agus Eko Sujianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The use of Zakat, Infaq and Sadaqah (ZIS) through the Madani Social Wallet in Bali plays a strategic role in alleviating poverty, increasing social welfare and building a sustainable community economy. Dompet Social Madani as the manager of ZIS is responsible for collecting, distributing and using funds effectively in accordance with Islamic Sharia principles. The use of ZIS in Bali is carried out through several stages starting from identifying mustahik, raising funds to implementing empowerment programs. Mustahik is the main beneficiary of ZIS distribution which includes the poor, orphans, widows and other vulnerable groups. Transparency and accountability in reporting fund management are important foundations for building public and donor trust in Dompet Social Madani. Madani Bali Social Wallet also integrates an economic empowerment approach in ZIS management. The empowerment program includes vocational training, support and business capital so that mustahik can be economically independent. In addition, part of the ZIS funds are allocated for the development of social infrastructure, such as building schools and other public facilities, to provide long-term benefits for the community. Collaboration with government, the private sector and other organizations is essential to increase the positive impact of ZIS. This collaboration optimizes resources and increases the efficiency of program implementation. Public education about the importance of zakat, infaq and shadaqah is also an integral part of the Bali Madani Social Wallet's efforts to expand reach and increase community awareness and involvement. One form of utilizing ZIS through the Madani Social Wallet in Bali is by establishing a Madani Health Institution which is realized in the form of a Madani Healthy House by not only collecting funds for aid, but also providing health services directly to the poor and underprivileged.